Responses of Aquatic Insect Functional Diversity to Landscape Changes in Atlantic Forest. (11th January 2013) - Colzani, Emílio; Siqueira, Tadeu; Suriano, Marcia T.; Roque, Fabio O.
Abstract The Atlantic Forest domain, one of the 25 world's hotspots for biodiversity, has experienced dramatic changes in its landscape. While the loss of species diversity is well documented, functional diversity has not received the same amount of attention. In this study, we evaluated functional diversity of insects in streams utilizing three indices: functional diversity (FD), functional dispersion (FDis), and functional divergence (FDiv), seeking to understand the roles of three predictor sets in explaining functional patterns: (1) bioclimatic and landscape variables; (2) spatial variables; and (3) local environmental variables. We determined the amount of variation in different measures of functional diversity that was explained by each predictor set and their interplays using variation partitioning. Our study showed that variation in functional diversity is better explained by a set of variables linked to different scales dependent on spatial structures, indicating the importance of landscape and mainly environmental variables in the functional organization of aquatic insect communities, and that the relative importance of predictor sets depends on the indices considered. Variation in FD was better explained by the interplay among the three predictor sets and by local environmental variables, whereas variation in FDis was better explained by spatial variables and by the interplay between environmental and spatial variables. Variation in FDiv was not significantly explained by any predictors. Our study adds more evidence on the harmful effects caused by landscape changes on biodiversity in the Atlantic Forest, suggesting that these effects also influence the functional organization of stream insect communities.